Manufacturing Refused Knowledge in the Age of Epistemic Pluralism Discourses, Imaginaries, and Practices on the Border of Science - Neresini, Federico; Agodi, Maria Carmela; Crabu, Stefano; Tosoni, Simone (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
This open access book explores contemporary practices that challenge science, arguing that this matter cannot be simply disregarded as a new manifestation of "anti-scientism". It scrutinizes the processes through which knowledge claims, refused by established institutions and the scientific community, seek legitimacy. Assuming an agnostic analytical stance, it explores the actors involved in such processes and their social worlds, their interactions with epistemic institutions, and the ways in which they enact such refused knowledge in their daily lives. Drawing on a three-year mixed-method research project, this collection demonstrates how refused knowledge can be seen as a distinct mode of knowing, employed in response to the uncertainties of everyday life. Thus, it offers a deeper understanding not only of how refused knowledge garners credibility, but also of how knowledge at large - including scientific knowledge - emerges from specific sociotechnical assemblages. Federico Neresini teaches Digital Sociology and Sociology of Innovation at the University of Padua, where he also coordinated the PaSTIS research unit. His research interests are focused on STS, in particular on the construction processes of scientific knowledge and the analysis of technoscience in the public sphere. Maria Carmela Agodi is Professor of Sociology and Science & Technology Studies at the University of Naples Federico II. Her recent research interests center around the epistemological and sociomaterial dimensions of robotic surgery, anti-aging medicine and practices, and on the institutional impact of global research regulation and local evaluation practices. Stefano Crabu is a science, technology and medicine sociologist at the University of Padova. He studies innovation processes in the life sciences and ICT, mainly focusing on the sociomaterial and epistemological aspects of translational biomedicine, laboratory practices and hacking practices. Simone Tosoni is Associate Professor at the Università Cattolica (Milan) where he teaches sociology of cultural processes and digital media. He is currently working on the hybridization of media and machines, on social robotics, and the online circulation of knowledge refused by the scientific community.